2004
DOI: 10.1124/jpet.104.074633
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the μ Opioid on Excitatory and Inhibitory Synaptic Inputs to Periaqueductal Gray-Projecting Neurons in the Amygdala

Abstract: Opioids are potent analgesics, but the sites of their action and cellular mechanisms are not fully understood. The central nucleus of the amygdala (CeA) is important for opioid analgesia through the projection to the periaquaductal gray (PAG). In this study, we examined the effects of opioid receptor stimulation on inhibitory and excitatory synaptic inputs to PAG-projecting CeA neurons retrogradely labeled with a fluorescent tracer injected into the ventrolateral PAG of rats. Whole-cell voltageclamp recordings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
56
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 42 publications
8
56
1
Order By: Relevance
“…Chieng et al (2006), however, demonstrated that approximately 20% of the cells in the medial portion of central nucleus showed responses to the DOR agonist deltorphin II (Chieng et al 2006), suggesting some populations of neurons within the amygdala are modulated by activation of DOR. Furthermore, these electrophysiological studies demonstrate that the opioid effects in this region are dependent upon characterization of the cell type in this area (Zhu and Pan 2004;Zhu and Pan 2005;Finnegan et al 2005;Chieng et al 2006), suggesting that opioid effects in the amygdalar circuitry might be very complex based on receptor-specific interactions with selective cell types. Although the specific mechanisms remain to be elucidated, the current data continue to suggest a critical interaction of amygdalar GABA/BZ and opioid systems in the anxiolytic actions of benzodiazepines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chieng et al (2006), however, demonstrated that approximately 20% of the cells in the medial portion of central nucleus showed responses to the DOR agonist deltorphin II (Chieng et al 2006), suggesting some populations of neurons within the amygdala are modulated by activation of DOR. Furthermore, these electrophysiological studies demonstrate that the opioid effects in this region are dependent upon characterization of the cell type in this area (Zhu and Pan 2004;Zhu and Pan 2005;Finnegan et al 2005;Chieng et al 2006), suggesting that opioid effects in the amygdalar circuitry might be very complex based on receptor-specific interactions with selective cell types. Although the specific mechanisms remain to be elucidated, the current data continue to suggest a critical interaction of amygdalar GABA/BZ and opioid systems in the anxiolytic actions of benzodiazepines.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that ENK overexpression could increase GABA release (Veinante et al 1997), thus enhancing the effectiveness of DZ at GABA A /BZ receptor sites. Several physiological studies in amygdala and periaqueductal gray, however, indicate that opioid agonists, including met-ENK, inhibit GABAergic neurotransmission via presynaptic effects although these effects are induced via activation of MOR receptors (Sugita and North 1993;Vaughan et al 1997;Finnegan et al 2005;Finnegan et al 2006). Although enkephalins interact with highest affinity at DOR, these opioid peptides do not show a large degree of discrimination for the three opioid receptor subtypes (Schoffelmeer et al 1990;Mansour et al 1995a;Mansour et al 1995b;Clarke et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…DAMGO application decreased inhibitory postsynaptic currents (IPSCs) in neurons projecting to the PAG, an effect that was blocked with the administration of bicuculline, a GABA A receptor antagonist. 111 The modulation of GABAergic neurotransmission by acute morphine appears to be mediated by a PTX-insensitive process. 112 The administration of RP-cAMPS triethylammonium, a cAMP inhibitor, reduced IPSC and attenuated morphineinduced GABAergic neurotransmission.…”
Section: Molecular Changes In the Amygdalamentioning
confidence: 99%
“…In an analogous manner, Zhu and Pan (2004) found that DAMGO evoked outward current in one type of CEA neurons (the so-called A1 cells), but that type B neurons showed no effect of MOR agonists (Zhu and Pan, 2004). Recordings from CEA neurons that selectively project to the ventrolateral periaqueductal gray (vlPAG) demonstrated that DAMGO decreased the frequency of inhibitory postsynaptic currents (IPSCs) in approximately half of these neurons, and also decreased IPSCs evoked by stimulation of the basolateral amygdala (Finnegan et al, 2005). Taken together, these studies demonstrate that distinct sets of neurons appear to respond to MOR agonists (Zhu and Pan, 2004;Chieng et al, 2006); that MOR agonists can reduce the activity of CEA projection neurons to the vlPAG, parabrachial nucleus, BNST, and thalamic reticular nucleus (Finnegan et al, 2005;Chieng et al, 2006); and that MOR agonists can also alter presynaptic release of GABA and glutamate in the amygdala (Finnegan et al, 2005(Finnegan et al, , 2006Zhu and Pan, 2005).…”
Section: Mor Activation Of Select Neuronal Populations Of the Amygdalamentioning
confidence: 99%
“…Electrophysiological studies in amygdalar slices have suggested that the effects of MOR agonists in CEA are dependent upon characterization of the cell type in this area (Finnegan et al, 2005;Pan, 2004, 2005;Chieng et al, 2006). In one study, DAMGO evoked an outward current in approximately 60% of CEA neurons that included cells projecting to several different nuclei, including BNST, parabrachial nucleus, and thalamic nuclei (Chieng et al, 2006).…”
Section: Mor Activation Of Select Neuronal Populations Of the Amygdalamentioning
confidence: 99%